Construction of Legislation Formation on Restorative Justice in the Neo-Classical Criminal Perspective of Law Number 1 of 2023 Concerning the Criminal Code - Nyoman Adi Arya Putra Dananjaya; I Nyoman Bagiastra (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
Restorative Justice is a process that involves both perpetrators or their families and victims or their families in the process of restoring conditions and rehabilitating perpetrators. This concept has fundamentally developed for a long time, but with the enactment of Law No. 1 of 2023 concerning the Criminal Code, it changes the punishment paradigm that was previously inspired by classical schools focusing on secular retribution, transforming by applying neo-classical schools that maintain balance between objective factors and subjective factors. However, regulatory provisions for restorative justice show disharmonies across investigation, prosecution, and judicial levels, requiring legal construction through expert doctrines and institutional regulations to create a comprehensive framework for applicable criminal cases. This research analyzes and constructs legal frameworks for implementing restorative justice within Indonesia's criminal law system under Law No. 1 of 2023, addressing regulatory disharmonies through neo-classical criminal law perspectives. This study employs normative legal research with a juridical normative approach, analyzing primary, secondary, and tertiary legal materials through literature study techniques. The research integrates statute, conceptual, historical, and comparative approaches to explore restorative justice application in Indonesia's criminal law system, including comparative analysis with Continental European countries. Current restorative justice regulations across investigation, prosecution, and judicial levels exhibit disharmony requiring legal construction through rechtsverfijning and comparative methods to align with the neo-classical paradigm of the 2023 Criminal Code.